Discovery of a Highly Specific and Potent Pan-RAF Inhibitor - Hong, Sung Pyo; Lee, Younho; Choi, Nam Song; Nam, Ky-Youb; Ahn, Soon Kil (Bulletin of the Korean Chemical Society, 2016)
We describe the structure‐based design and synthesis of N‐(2,6‐difluorophenyl)‐3‐(9H‐purin‐6‐yl)pyridine‐2‐amine derivatives as a selective pan‐RAF kinase inhibitor. The synthesized compounds showed highly potent and specific inhibition of the BRAFV600E mutant cell line. Among them, N‐(3‐((3‐(9H‐purin‐6‐yl)pyridine‐2‐yl)amino)‐2,4‐difluorophenyl)furan‐3‐sulfonamide (4b) exhibited the most potent inhibitory activities against protein kinase enzymes BRAFV600E, BRAFWT, and CRAF (IC50 of 2, 2, and 1 nM, respectively) and a mutant cell line bearing a BRAFV600E mutation, A375P (GI50 of 7 nM).